2021
DOI: 10.9758/cpn.2021.19.3.434
|View full text |Cite
|
Sign up to set email alerts
|

Consideration of Long-Acting Injectable Antipsychotics for Polypharmacy Regimen in the Treatment of Schizophrenia: Put It on the Table or Not?

Abstract: Antipsychotic monotherapy (APM) is considered best-acceptable treatment option regardless of antipsychotic class and formulation types for treating schizophrenia. However, antipsychotic polypharmacy (APP) has been also widely utilized in routine clinical practice. Despite APP has some clinical benefits it has also numerous pitfalls in relation with increased total number and doses of APs leading to adverse events as well as decrease of treatment adherence and persistence resulting in poor clinical outcomes. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 92 publications
0
7
0
Order By: Relevance
“…Although not the focus of this study, we also found that the proportion of individuals who had used an oral SGA was quite high in the pre- and post-index period, while those who used a FGA both oral or LAI was low. These findings may reflect prescribing practices where individuals are generally initiated on a LAI formulation of the corresponding current oral antipsychotic, and while polypharmacy between different types and formulations of antipsychotics is not uncommon, the same type of LAI and oral are generally prescribed together [ 24 26 ]. These findings may warrant inquiry in future work examining antipsychotic medication treatment patterns and prescribing practices among individuals initiating LAIs; for those also under an active CTO, understanding which antipsychotics, if any, are included within the treatment plan would provide additional insight.…”
Section: Discussionmentioning
confidence: 99%
“…Although not the focus of this study, we also found that the proportion of individuals who had used an oral SGA was quite high in the pre- and post-index period, while those who used a FGA both oral or LAI was low. These findings may reflect prescribing practices where individuals are generally initiated on a LAI formulation of the corresponding current oral antipsychotic, and while polypharmacy between different types and formulations of antipsychotics is not uncommon, the same type of LAI and oral are generally prescribed together [ 24 26 ]. These findings may warrant inquiry in future work examining antipsychotic medication treatment patterns and prescribing practices among individuals initiating LAIs; for those also under an active CTO, understanding which antipsychotics, if any, are included within the treatment plan would provide additional insight.…”
Section: Discussionmentioning
confidence: 99%
“…Most treatment guidelines state that APM should be the first-line treatment and APP should be a treatment strategy of last resort for treatment-resistant schizophrenia [ 2 - 10 ]. They stated that clozapine should be tried in the first place to overcome inadequate treatment response from different APM trials.…”
Section: When and How To Initiate App?mentioning
confidence: 99%
“…However, the efficacy of antipsychotic therapy is not satisfactory in real world by which many next treatment strategies have been utilized in routine practice for offering better treatment outcomes for patients with schizophrenia, although some second treatment options such as antipsychotic polypharmacy (APP) are not officially recommended by major treatment guidelines or fully supported by evidence-based data from randomized controlled, clinical trials (RCTs), cohort study and adequately-powered, well-designed practical trials [ 3 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, at least 20% of patients with schizophrenia do not have a sufficient response to APM ( Asenjo Lobos et al , 2010 ; Okhuijsen-Pfeifer et al , 2018 ). Approximately 34% of patients with schizophrenia do not respond to the first- and second-line treatment with antipsychotics, and they are therefore classified as treatment-resistant schizophrenia (TRS) cases ( Pae et al , 2021 ). This is one of the reasons why antipsychotic polypharmacy (APP) is commonly prescribed in clinical practice (i.e.…”
Section: Introductionmentioning
confidence: 99%